Skipping Posterior Dynamic Transpedicular Stabilization for Distant Segment Degenerative Disease - Bilgehan Solmaz; Ahmet Levent Aydin; Cengiz Gomleksiz; Yaprak Ataker; Mehdi Sasani; Tunc Oktenoglu; Ali Fahir Ozer (Advances in Orthopedics)
Objective. To date, there is still no consensus on the treatment of spinal degenerative disease. Current surgical techniques to manage painful spinal disorders are imperfect. In this paper, we aimed to evaluate the prospective results of posterior transpedicular dynamic stabilization, a novel surgical approach that skips the segments that do not produce pain. This technique has been proven biomechanically and radiologically in spinal degenerative diseases. Methods. A prospective study of 18 patients averaging 54.94 years of age with distant spinal segment degenerative disease. Indications consisted of degenerative disc disease (57%), herniated nucleus pulposus (50%), spinal stenosis (14.28%), degenerative spondylolisthesis (14.28%), and foraminal stenosis (7.1%). The Oswestry Low-Back Pain Disability Questionnaire and visual analog scale (VAS) for pain were recorded preoperatively and at the third and twelfth postoperative months. Results. Both the Oswestry and VAS scores showed significant improvement postoperatively (P<0.05). We observed complications in one patient who had spinal epidural hematoma. Conclusion. We recommend skipping posterior transpedicular dynamic stabilization for surgical treatment of distant segment spinal degenerative disease.